(3MhGT Ydi TQM JdNjU GdeaJGMs - (3GdLQLGfj, GdTQja, Ydj Hf eMeO Hf Ydj, J (B816 (3g`s ((3Ndjd Hf Ydj Hjc GdMjaj GdJhfjs)
(3ChdgG (B:s
(3GdMeO ddg (B... (3gPg MhGT cfJ bO bjOJgG Ydjg eLedI MGd HEbQGAg Ydi HYV CMHJj aSCdhfj (B.. (3Cf CaUdgG dge hCfbO eG aYdJ Pdc eSJYjfG HGddg heJhcdG Ydjg (B...s
(3BNQgG (B:s
... (3GdcejJ hGdCTYQ heKd GdGdNjaGA (B.. (3aQS CNja Hjf GdNja EPG cGf EMOi Yjfjg RQbGA hGdCNQi ShOGA heKd GdQbWGA ShGO jThHg fbW hHjGV (B. (3OLGLI QbWGA , hGddg CYdes
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ddRQcdj (B5/7s
(3cTa GdXfhf (B1/473s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdHdGZIs